2002
DOI: 10.1183/09031936.02.00203502
|View full text |Cite|
|
Sign up to set email alerts
|

Physical exercise, sports, and lung function in smokingversusnonsmoking adolescents

Abstract: Associations between adolescent smoking habits and exercise, particularly participation in sports and lung function were studied.All students aged 13-19 yrs in Nord-Trøndelag County, Norway, 1995, were invited to join a cross-sectional study. Information on smoking habits and exercise was obtained by self-administered questionnaire. Spirometry was performed in accordance with American Thoracic Society standards.Of the 6,811 students (aged 13-18 yrs, without asthma), 2,993 (44%) reported neversmoking, and 1,342… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
51
1
13

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(75 citation statements)
references
References 30 publications
10
51
1
13
Order By: Relevance
“…The findings are in agreement with the observations from the other study carried out on adolescent males and females depicting that as the exercise level increases, FVC, FEV 1 value increases [11]. PEFR, an effort dependent value which can easily detect airway obstruction, is higher in DG study participants compared to their CG counterparts; this finding is in consonance with the observations of Chaitra et al [10] in which moderate intensity aerobic training of young Indian males improved pulmonary function variables FVC, FEV 1 , and PEFR but not FEV 1 %.…”
Section: Discussionsupporting
confidence: 82%
“…The findings are in agreement with the observations from the other study carried out on adolescent males and females depicting that as the exercise level increases, FVC, FEV 1 value increases [11]. PEFR, an effort dependent value which can easily detect airway obstruction, is higher in DG study participants compared to their CG counterparts; this finding is in consonance with the observations of Chaitra et al [10] in which moderate intensity aerobic training of young Indian males improved pulmonary function variables FVC, FEV 1 , and PEFR but not FEV 1 %.…”
Section: Discussionsupporting
confidence: 82%
“…This attitude is also detected in a study of 1,462 students from Italy, where the correlation between exercise and smoking showed that whereas smoking incidence increases according to age, exercising persons present an opposite trend [14]. Also, the frequency of physical exercise is inversely associated with smoking [15]. Participating in exercise and avoiding smoking are linked.…”
Section: O P Y R Ig H T G E N E R a L P R A C T Ic E A Ir W A Y S Gmentioning
confidence: 71%
“…9,10 Esperava-se encontrar uma associação entre tabagismo e sedentarismo, pois o tabagismo é descrito como mais prevalente em indivíduos sedentários e o exercício físico é considerado fator protetor contra seu início. 10,18 A não associação encontrada no presente estudo pode estar relacionada ao baixo consumo diário, uma vez que 69,8% da amostra estudada consome menos que 10 cigarros por dia. Segundo Scobedo et al, 6 o baixo consumo pode difi cultar a identifi cação de associação entre atividade física e tabagismo.…”
Section: Discussionunclassified
“…17 Alguns estudos relatam associação entre sedentarismo e tabagismo. 10,18 Adolescentes fumantes apresentam menores níveis de atividade física, e a atividade física na adolescência interfere no início do tabagismo neste período e em sua manutenção na idade adulta. 9 Além das possíveis associações entre a gênese do tabagismo e do sedentarismo, a prática regular de exercícios físicos pode colaborar para o abandono do hábito tabagístico.…”
unclassified